The Structure and Growth of the Canadian National Unions - Chaison, Gary; Rose, Joseph (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 1981)
The authors present an overview of union growth and high-light specific characteristics of national trade unions, review recent studies of union growth in Canada, examine their relevance to the rise of national unionism, develop an alternative model of union growth and test its applicability to national unions.